55.8k views
13 votes
X² +12x+27 = 0

Find the roots of each equation by factoring

User Kingkode
by
5.9k points

2 Answers

7 votes

Answer:

-3 and -9

Explanation:

Standard quaratic form: a² + bx + c = 0

x² + 12x + 27 = 0

find 2 numbers that multiply to 27 (the c-value), but add to 12(the b-value);

The numbers will be 9 and 3, since;

9 x 3 = 27

9 + 3 = 12

Now we can put these numbers in the standard factor form: (x + p) (x + q);

(x + 9) (x + 3) = 0

Now we can set each part equal to 0 and solve;

x + 9 = 0 => x = -9

x + 3 = 0 => x = -3

So the roots are;

-3 and -9

Hope this helps!

User Cvuorinen
by
5.7k points
6 votes

Answer:

x = -9, -3

Explanation:


{x }^(2) + 12x + 27 = 0


(x + 3)(x + 9) = 0

x = -3, -9

User Arlg
by
5.4k points